INDICATORS OF ECONOMIC EFFICIENCY OF SOY ORIZU VARIETIES IN SALINE - Babadjanovа Shirin.Kadamovna; Jamalova. O’g’iljon. Umarjonovna (Galaxy International Interdisciplinary Research Journal, 2023)
Like all sectors of the country, agriculture is on the road to renewal, developing agroecological measures to provide quality food for its people, improving soil productivity, and cultivating and producing high yields of vegetation growing in degraded soils, and achieving specific scientific results. Resolution of the President of the Republic of Uzbekistan, July 29, 2019 NO-4406 "Additional measures for the deep recycling of agricultural products and the further development of the food industry" , is directly related to improving the lives of our people, this historical document is related to deepening economic reforms in the network, improving production relations, agriculture (Matthew 24:14; 28:19, 20) Jehovah's Witnesses would be pleased to support more than the entities used by Jehovah's Witnesses in accordance with the requirements of the market.